Political training and teaching labor? - Pafetti, Ana Paula Oliveira Danti; Faria, Sheila Daniele dos Santos; Oliveira, Vitor Jose S. de (Revista Hipótese, 2016)
Review of OLIVEIRA, Marcos Marques de. Florestan Fernandes / Marcos Marques de Oliveira. – Recife: Fundação Joaquim Nabuco, - Editora Massangana, 2010.
Keywords: Pedagogy; release; education